TANGGUNG JAWAB NEGARA TERHADAP PEMENUHAN HAK KESEHATAN JIWA DI MASA PANDEMI COVID-19 DALAM PERSPEKTIF HAK ASASI MANUSIA - Rani Rinaldi; Dodi Haryono; Muhammad A. Rauf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Fulfillment of mental health rights before the pandemic still had problems that had notbeen resolved by the government, until the emergence of the Covid-19 pandemic mental healthincreasingly did not receive the government's attention, causing significant problems. Laws andregulations that legitimize that mental health is health that must be considered like physicalhealth, have not been sufficiently implemented because the government has not made mentalhealth a top priority in handling a pandemic.This type of research can be classified as normative research, because in this study theauthor examines legal theories and principles and examines literature based on legalsystematics. Sources of data used, primary data, secondary data and tertiary data. Datacollection techniques in this research with literature studies found general concepts related toresearch problems.From the research results there are three main things that can be concluded. First, theright to get fulfillment of mental health during the Covid-19 pandemic is a guarantee that cannotbe released and is the responsibility of the state. Second, the mental health law is considered tostill have limited regulations regarding the fulfillment of mental health rights during the Covid-19 pandemic. Third, there needs to be a change in the rules because ideally a law and regulationalways experiences continuous development. Author's suggestion, First, the government needs tocarry out mental health management in a planned manner to thoroughly evaluate theimplementation of mental health rights during the Covid-19 pandemic. Second, the governmentin its active character needs to be required to carry out governmental tasks in accordance withthe authority it has.Keywords: State responsibility - Mental Health - Covid-19 Pandemic - Human Rights